La Influencia De La Recreacion En El Aumento De La Produccion Y El Mejoramiento De La Calidad De Vida De Los Empleados De La Fabrica Muebles Del Quindio (2002)
Leaving or the preleaving of the premise that the recreation allows to improve the quality of the individuals’ life since it contributes in the development psicosocial of who practice it, of investigating the influence that can have the recreational programs into the organizations for it we account with of the directives of it of the fábrica Muebles del Quindio of the Armenia city they considered interesting the possibility to create mechanisms that allowed them to improve the yield of workers give them the possibility to be developed integrally. The biggest obstacle that was presented in the development of the investigation was the lack of convincing on the part of the workers, about the benefits that one every can obtain through the recreation practiced during the labor day, however, as they done diverse activities, it was possible to capture your attention, getting this way that all the workers participated and they collaborate in the investigative work. Also on the part of the directive of it factory we got the recognition of the importance of the recreational programs that allow the humanization of the work and the productive efficiency.